Propuesta de identidad de marca para los equipos deportivos de la Universidad Antonio Nariño paras las sedes de la ciudad de Bogotá. (2023)
This project consists of generating a proposal for sports brand identity for the teams where students of the Universidad Antonio Nariño (UAN) participate. Since the university does not have a well-structured brand identity in the area of sports. In this way we seek to contribute to the university teams, from the perspective of graphic design, it is expected to establish an equitable approach to work with all university teams, avoiding preferences to one or another, presenting a collaborative and distinctive modality.